"Geo-characterization" of selected areas in Crete, Greece, towards realistic assessment of seismic design actions - Vafidis, A.; Steiakakis, M.; Agioutantis, Z.; Andronikidis, N.; Kritikakis, G.; Economou, N.; Pandi, K.; Spanoudakis, N.; Savvaidis, A.; Margaris, B.; Theodoulidis, N.; Lekidis, V.; et al. (Bulletin of the Geological Society of Greece, 2013)
The geo-characterization of site conditions is crucial for the estimation of regional elastic spectra. The work to be done in the framework of the “GEO-CHARACTERIZATION” THALIS-project, will combine geotechnical and geophysical methods and evaluate them to estimate critical geotechnical parameters. Although geotechnical tests in lab may provide more accurate estimates of geotechnical parameters, they require costly and time consuming drilling procedures. On the other hand geophysical methods are useful in providing estimates in situ of subsurface physical properties, which are not directly related to geotechnical parameters. Within “GEO-CHARACTERIZATION” THALIS-project a pilot survey for geotechnical characterization at selected sites of Hellenic Accelerometric Network in Crete will be conducted by employing geotechnical, geological and geophysical techniques. Subsequently, by correlating “geo-data” collected within this project, relations of certain mechanical parameters obtained in laboratory or/and in situ with geophysical parameters for typical geologic formations and soils will be established. The “GEO-CHARACTERIZATION” project, will focus on the influence of dynamic loads on geotechnical phenomena related to the static stress field variation, the estimation of site effects due to seismic motion and the proposal of regional elastic spectra for seismic provisions as well as their comparison with the corresponding elastic design spectra of Eurocode 8 (EC8).